Factors influencing public expenditure on education in Guyana (1953-1967) - Anderson, Wolseley W. (1971)
This study investigated the pattern and levels of public expenditure on primary, secondary, and teacher education in Guyana during the period 1953-1967. This period coincided with Guyana's transition from colonialism to political independence, and the context of educational spending decisions was that of a culturally plural society, in which religious differentiation, political identification along racial lines, and the traditional influence of Christian denominational involvement in schools' provision and control--the Dual Control System--all co-existed. Within this context, and employing both normative theory and fiscal sociology, the study revealed that the three most powerful factors determining public expenditure on education were: 1) rapid population growth, 2) the changing political climate that determined periodically what decisions were made and implemented, and 3) a productivity factor that had to do with the efficiency level in the various sections and sub-sections of the formal educational system
Keywords: Educational costs